2013
DOI: 10.1093/jxb/ert284
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic and transcriptomic approaches to address the active role of GA4 in Japanese apricot flower bud dormancy release

Abstract: Hormones are closely associated with dormancy in deciduous fruit trees, and gibberellins (GAs) are known to be particularly important. In this study, we observed that GA4 treatment led to earlier bud break in Japanese apricot. To understand better the promoting effect of GA4 on the dormancy release of Japanese apricot flower buds, proteomic and transcriptomic approaches were used to analyse the mechanisms of dormancy release following GA4 treatment, based on two-dimensional gel electrophoresis (2-DE) and digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 41 publications
8
90
0
Order By: Relevance
“…These results indicated that the accumulation of transcripts and proteins occur independently. A generally low congruency of proteomic and transcriptional profiles has been reported in other previous studies (Lan et al, 2011; Zhuang et al, 2013). …”
Section: Resultssupporting
confidence: 46%
“…These results indicated that the accumulation of transcripts and proteins occur independently. A generally low congruency of proteomic and transcriptional profiles has been reported in other previous studies (Lan et al, 2011; Zhuang et al, 2013). …”
Section: Resultssupporting
confidence: 46%
“…There is accumulating evidence of the possible involvement of MADS-box genes and other flowering-related genes in dormancy regulation (Horvath, 2009). Furthermore, recent genome-wide transcriptomic studies have suggested significant roles for phytohormones in the dormancy phase transition of various plant species Díaz-Riquelme et al, 2012;Gai et al, 2013;Habu et al, 2014;Liu et al, 2012;Zhong et al, 2013;Zhuang et al, 2013a). Although this review focused on bud dormancy regulation, dormancy is not only a trait of bud phenology but one of the seasonal growth-regulatory phases for entire trees;…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%
“…Rinne et al (2011) consideredthe function of GA 3 and GA 4 in dormancy is distinguished, and only GA 4 can better replace part of the chilling requirement. In the previous studies, our group has proved that GA 4 , as a good dormancy breaker, can replace a part of chilling requirements and cause an early release of dormancy in Japanese apricot (Zhuang et al, 2013). DELLA (Asp-Glu-Leu-Leu-Ala) is a crucial negative regulatory element of the GA signal transduction pathway, which is a subfamily of the GRAS gene family (Salanenka et al, 2018; Nimisha et al, 2013).…”
Section: Introductionmentioning
confidence: 98%